The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1590/s1415-43662004000100006
|View full text |Cite
|
Sign up to set email alerts
|

Acumulação de nitrogênio e carbono no solo pela adubação orgânica e mineral contínua na cultura do milho

Abstract: No presente trabalho, avaliou-se o efeito do uso contínuo das adubações orgânica e mineral na cultura do milho e sobre a acumulação e a disponibilidade do nitrogênio em um Argissolo Vermelho-Amarelo. Estudou-se a produção de milho em função das doses de 0 e 40 m³ ha-1 ano-1 de composto orgânico (palhada de soja e feijão com esterco bovino), combinadas com 0, 250 e 500 kg ha-1 ano-1 da fórmula 4-14-8 aplicados no plantio, e 0, 100 e 200 kg ha-1 ano-1 de sulfato de amônio em cobertura. O uso contínuo da adubação… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 12 publications
0
3
0
1
Order By: Relevance
“…Positive effect of soil N inputs with application of crop residues also is showed in literature 30,31 , as well the positive effect of N mineral fertilizer [32][33][34] . In our study, the application of crop residues increased 87% of total N in soil, while N mineral fertilize increased 61% of total N in soil, and association of crop residue and N mineral fertilizer contributed in 90%.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Positive effect of soil N inputs with application of crop residues also is showed in literature 30,31 , as well the positive effect of N mineral fertilizer [32][33][34] . In our study, the application of crop residues increased 87% of total N in soil, while N mineral fertilize increased 61% of total N in soil, and association of crop residue and N mineral fertilizer contributed in 90%.…”
Section: Discussionmentioning
confidence: 72%
“…Increasing of soil N with mineralization of soybean residues was presented by 14,15,42 . 30 showed that compost application of beans and soybean residues and manure increased 44 and 27% of total organic nitrogen in soil layer 0.0-0.1 and 0.1-0.2 m, respectively compared to soil without N application. In our study, the highest decrease of N in remaining residue corroborated the N addition in soil by mineralization of soybean with a correlation of 99% (Pearson correlation).…”
Section: Discussionmentioning
confidence: 99%
“…The plant biomass increased the amount of nutrients in the soil, which resulted in a corn yield increase from 4.2 t ha −1 in (soil fertilized with cattle manure) to 7.7 t ha −1 (soils with macrophyte). The continuous use of organic fertilizer increased corn productivity compared to chemical fer-tilizer, as reported by Maia and Cantarutti (2004).…”
Section: Ammentioning
confidence: 87%
“…Já onde houve aplicação de N em cobertura a taxa de incremento na produtividade foi de 14,76 kg, observando assim que a adubação nitrogenada contribui menos para o aumento da produtividade quando há interação entre adubação orgânica e mineral, efeito este também observado por Maia e Cantarutti, (2004). Silva et al (2007) afirmam que o uso contínuo da adubação organomineral na cultura do milho, provoca aumentos significativos por vários anos na produção de grãos.…”
Section: F V G L N Em Coberturaunclassified